Training in Integrative Therapies Increases Self-Efficacy in Providing Nondrug Therapies and Self-Confidence in Offering Compassionate Care - Kathi J. Kemper MD, MPH; Ellie Hill (SAGE Publishing, 2017)
Background. Patient demand and clinician interest have driven professional training in integrative therapies, but few rigorous evaluations have been published. Methods. This project evaluated the proof of concept of training in acupressure, guided imagery, massage, and Reiki on clinicians' sense of self-efficacy in providing nondrug therapies, self-confidence in providing compassionate care, and engagement with work. Results. Three out of 4 topics met minimum enrollment numbers; 22 of 24 participants completed follow-up as well as pretraining surveys. All would recommend the training to others and planned changes in personal and professional care. There were significant improvements in self-efficacy in using nondrug therapies, confidence in providing compassionate care, and unplanned absenteeism ( P < .05 for each). Conclusion. Training in integrative therapies is feasible and associated with significant improvements in clinicians' sense of self-efficacy, confidence in providing compassionate care, and engagement with work. Additional studies are needed to determine the impact on quality of care and long-term workforce engagement.